1983
DOI: 10.3949/ccjm.50.2.239
|View full text |Cite
|
Sign up to set email alerts
|

The psychodynamics of tattooing: a review

Abstract: The ancient art of tattooing has diverse meanings. In the South Seas archipelagos and in some Asian civilizations (India, Burma, and Japan) it has religious significance and is prized as a means of adornment. The intense pursuit of identity and autonomy that occurs during adolescence brings to the surface subconscious feelings, particularly of aggression and sexuality. These are often expressed by a rebellion against the standards of authority. A dramatic and indelible manner of expressing these conflicts is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Today tattooing in the Western world is considered to be a sign of self-destructive and rebellious behaviour [1]. Kilmer et al [2] estimated that approximately 10 million people in the United States have at least one decorative tattoo.…”
Section: Introductionmentioning
confidence: 99%
“…Today tattooing in the Western world is considered to be a sign of self-destructive and rebellious behaviour [1]. Kilmer et al [2] estimated that approximately 10 million people in the United States have at least one decorative tattoo.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who choose to be tattooed may get their first tattoo when they are as young as 10 ( Armstrong & McConnell 1994). Much earlier literature about tattooing among adolescents was based on substance abuse treatment programme and detention centers ( Burma 1959, Taylor 1968, Verberne 1969, Thomson & McDonald 1983, Fried 1983, Davies 1991, Farrow et al 1991 ). Findings from these studies suggested that tattooed adolescents were from a lower socioeconomic status and were involved in socially deviant behaviours and lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of tattoos – conscious and unconscious alike – are multifaceted. Extensive historical, sociological, and psychological research delineates the significance tattoos have had for various peoples and contexts throughout the history of the phenomenon (Fried, 1983; Grumet, 1983; Kächelen, 2004; Oettermann, 1994; Rosenblum, 1999; Stirn, 2002). Interestingly, most of this research concerns itself almost exclusively with the conscious implications of tattooing practices – almost as if tattooing seductively invites a single‐minded focus on the conscious and the concrete.…”
mentioning
confidence: 99%